Assessing Strain Rate Sensitivity of Nanotwinned Al–Zr Alloys through Nanoindentation - Nicholas Allen Richter; Xuanyu Sheng; Bo Yang; Benjamin Thomas Stegman; Haiyan Wang; Xinghang Zhang (Crystals, 2023)
Nanotwinned metals have exhibited many enhanced physical and mechanical properties. Twin boundaries have recently been introduced into sputtered Al alloys in spite of their high stacking fault energy. These twinned Al alloys possess unique microstructures composed of vertically aligned Σ3(112) incoherent twin boundaries (ITBs) and have demonstrated remarkable mechanical strengths and thermal stability. However, their strain rate sensitivity has not been fully assessed. A modified nanoindentation method has been employed here to accurately determine the strain rate sensitivity of nanotwinned Al–Zr alloys. The hardness of these alloys reaches 4.2 GPa while simultaneously exhibiting an improved strain rate sensitivity. The nanotwinned Al–Zr alloys have shown grain size-dependent strain rate sensitivity, consistent with previous findings in the literature. This work provides insight into a previously unstudied aspect of nanotwinned Al alloys.